Kaposi Sarcoma in Kidney Transplanted Patients - Shahbazian, Heshmatollah (Urology Journal, 2009)
Purpose: Newly developed malignancies in kidney transplanted patients are one of the complications attributed to immunosuppression. Kaposi sarcoma is an unusual malignancy in general population, but may develop in kidney transplanted patients with highly varying prevalence. Our aim is to evaluate the prevalence, clinical manifestations, and outcome of Kaposi sacoma in kidney transplanted patients. Materials and Methods: Five hundred and eighty cases (330 male, 250 female) with a mean age of 38.2 were followed for 36 months (range 9 months to 10 years), visiting every two months. History taking and physical examination with emphasis on skin and mucosa were taken. Biopsy of suspicious sin, mucosal, and visceral lesions assigned by other paraclinical methods was performed. Except 7 cases which were HLA identical to donors, all patients were managed with cyclosporine, Azathioprine and Prednisolone. Results: Fourteen patients (2.2%) developed Kaposi sarcoma (biopsy documented which constituted 60% of all post-transplantation malignancies. They were 11 males and 3 females with a mean age of 41 years. Sarcoma developed 8 to 31 months after transplantation with an average of 18 months. Of these patients, 13 had skin involvement that one of them had pulmonary involvement too. Another patient had only abdominal involvement. Azathioprine was discontinued all patients, and cyclosporine was reduced in skin affected patients. In patients with visceral involvement cyclosporine was discontinued and then chemotherapy was initiated. All 3 patients with visceral involvement didn’t respond to chemotherapy and expired after 6 months. Of 11 patients with skin involvement, one had complete and 2 had incomplete remission of whom, one expired due to acute rejection. Renal function in 8 patients was acceptable, but 2 had impaired renal function, yet didn’t need dialysis. Conclusion: Prevalence of Kaposi sarcoma in our patients is more than western countries. Visceral involvement is uncommon. But has poor prognosis. Reducing immunosuppression with discontinuation of azathioprine and significant reducing cyclosporine dosage can cease skin evolvement, with preserving renal function in most of the patients.